Pengaruh Loan to Deposit Ratio, Capital Adequacy Ratio, dan Return On Equity Terhadap PT.Bank Central Asia Tbk Periode 2017-2022 - Anugrah Maulidi Sudirman (OPTIMAL Jurnal Ekonomi dan Manajemen, 2024)
This research aims to determine and analyze the influence of the Loan to Deposit Ratio, Capital Adequacy Ratio, and Return on Equity on the share price of PT Bank Central Asia Tbk for the 2017-2022 period. This research uses a quantitative method with an associative approach which aims to determine the influence of the independent variable on the dependent variable and how big the influence of two or more variables is. The type of data used is quantitative data with secondary data sources consisting of financial report data from PT. Bank Central Asia Tbk 2017-2022 period. The analytical method used is multiple linear regression, t test and f test to obtain results regarding the influence of the independent variable on the dependent variable. The research results show that partially the Loan to Deposit Ratio is positive but not significant, the Capital Adequacy Ratio partially has a significant negative effect while the Return On Equity has a significant positive effect. Meanwhile, simultaneously the Loan to Deposit Ratio, Capital Adequacy Ratio and Return On Equity together -the same has a positive and significant effect.